Influence of Different Vegetable Oils on In Vitro Ruminal Fermentability and Nutrient Digestibility in Ettawah Crossbred Goat - Muktiani, Anis; Arifah, Nurul; Widiyanto, Widiyanto (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
This research was aimed to determine the effect of supplementation of vegetable oil (corn oil, palm oil and kapok seed oil) on in vitro ruminal fermentability and nutrient digestibility. Experiment design used was Randomized Block Design with four treatments and four replication based on rumen fluid sampling time. The four treatments namely R0 = feed without oil supplementation; R1 = R0 + 5% corn oil; R2 = R0 + 5% palm oil; and R3 = R0 + 5% kapok seed oil. The result showed that supplementation of 5% vegetable oil did not affect (P>0,05) the rumen pH, A/P ratio, and efficiency of energy conversion. The total VFA, acetate, propionate, butyrate, methane and NH3 was higher (P<0,05) in supplementation of 5% vegetable oil than he control. The population of protozoa, microbial protein, in vitro dry matter digestibility (IVDMD), organic matter digestibility (IVOMD), and crude fiber digestibility (IVCFD) was lower (P<0,05) in supplementation of 5% compared to the control. Population of protozoa decreased until 58,76% for R1; 66,89% for R2; and 43,33% for R3. It can be concluded that supplementation of 5% vegetable oil decreased the population of protozoa, increased the production of VFA and NH3. Supplementation of 5% kapok seed oil resulting the highest of total VFA, acetate, propionate, butyrate and NH3 among other treatments.